Pengaruh Pembelajaran VCT Terhadap Peningkatan Pemahaman Nasionalisme Siswa Kelas XI IPS MAN 2 Bandar Lampung - Suciana Suciana; Henry Susanto; Yustina Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2019)
The Aim of this paper is to determine whether there is an influence between the VCT (Value Clarification Technique) Learning Approach Against Improvement in Nationalism of eleventh grade students of social studies one, MAN 2 Bandar Lampung in Academic Year 2018/2019